RTI implementation at the district level: Issues and challenges - Jain, Abhishek (2009)
An attempt has been made to identify issues and constraints in the implementation of the Right to Information Act. Since the implementation of the Act at the district level is the most vital link in the chain of information sharing within the national and sub-national framework, the study examines the issues faced from the demand and supply sides which need to be addressed at the district level for effective implementation of the Act. - Reproduced.
Keywords: Right to information